A Single‐Device Universal Logic Gate Based on a Magnetically Enhanced Memristor. (23rd October 2012) - Prezioso, Mirko; Riminucci, Alberto; Graziosi, Patrizio; Bergenti, Ilaria; Rakshit, Rajib; Cecchini, Raimondo; Vianelli, Anna; Borgatti, Francesco; Haag, Norman; Willis, M.; Drew, Alan J.; Gillin, William P.; et al.
<x xml:space="preserve">Abstract</x> Memristors are one of the most promising candidates for future information and communications technology (ICT) architectures. Two experimental proofs of concept are presented based on the intermixing of spintronic and memristive effects into a single device, a magnetically enhanced memristor (MEM). By exploiting the interaction between the memristance and the giant magnetoresistance (GMR), a universal implication (IMP) logic gate based on a single MEM device is realized. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>